KINESIOLOGY TAPING AND NEURAL GLIDING EXERCISE IN CARPAL TUNNEL SYNDROME - Deby Wahyuning Hadi & Amanda Tiksnadi (International Journal of Research Science and Management, 2020)
Introduction: Carpal Tunnel Syndrome (CTS) is a condition of neuropathy caused by median nerve entrapment, which is related to repetitive injury mostly due to workload. Some people have occupation that require a lot of repetitive wrist movement such as cigarette factory workers. Kinesiology taping and neural gliding exercises are conservative interventions, which can be performed on people with CTS. Case: This case report showed that there was improvement symptom of carpal tunnel syndrome treated with kinesiology taping and neural gliding exercise. The patient was female, 43 years old, a cigarette factory worker. She had complains of tingling sensation on her palms, moreover on finger 1, 2 and 3 since 2 weeks before. The physical examination revealed positive test of carpal tunnel syndrome such as Phalen, Pressure Provocation and Tinel test. Boston Carpal Tunnel Questionnaire (BCTQ) was also performed. The diagnose was confirmed with nerve conduction studies result. Kinesiology taping was applied on this patient and reapplied weekly until 4 weeks. Patient was also taught about neural gliding exercise and was asked to do it every day for 4 weeks. BCTQ was evaluated weekly and improved every week. While nerve conduction studies was evaluated in 4 weeks and there was also improvement in the result. Conclusion: The improved outcome occurring in this case shows that kinesiology taping and neural gliding exercise can be considered as management of carpal tunnel syndrome, but of course further research is needed to prove its significance.